Does fertility-specific distress vary by race/ethnicity among a probability sample of women in the United States?. (February 2016) - Greil, Arthur L; McQuillan, Julia; Sanchez, Delida
This study explored whether fertility-specific distress varied by race/ethnicity among a nationally representative sample of US women. Participants were 2363 White ( n = 1266), Black ( n = 569), Hispanic ( n = 453), and Asian ( n = 51) women who participated in the National Survey of Fertility Barriers. Participants were given the Fertility-Specific Distress Scale and assessed for strength of pregnancy intent, primary versus secondary infertility, and socioeconomic hardship. Black women reported lower levels of fertility-specific distress than White women, but these were fully mediated by the strength of pregnancy intentions. Primary versus secondary infertility and economic hardship were not associated with fertility-specific distress.